New directions in Jewish philosophy - Hughes, Aaron W.; Wolfson, Elliot R. (Indiana University Press, 2010)
Screening the canon: Levinas and medieval Jewish philosophy / Martin Kavka -- Precursorship and the forgetting of history: Franz Rosenzweig and Saadya Gaon on the memory of translation / Aaron W. Hughes -- Light does not talk but shines: apophasis and vision in Rosenzweig's theopoetic temporality / Elliot R. Wolfson -- Textual body landscapes and the artist's geometry of Talmud: atelier-work with the materiality of scripture / Almut Sh. Bruckstein -- Construction of animals in medieval Jewish philosophy / Kalman P. Bland -- Sharing secrets: inter-confessional philosophy as dialogical practice / Steven M. Wasserstrom -- Ethical-political universality out of the sources of Judaism: reading Hermann Cohen's 1888 affidavit in and out of context / Dana Hollander -- What is the sophist? Who is the rabbi? / Sergey Dolgopolski -- Forging a new righteous nation: Maimonides' midrashic interweave of verse and text / James A. Diamond -- Aesthetics and the infinite: moses mendelssohn on the poetics of biblical prophecy -- Michah Gottlieb